BUILDING FEASIBILITY STRATEGIC QUALITY IMPROVEMENT OF HIGHER EDUCATION THROUGH INTERNAL QUALITY ASSURANCE SYSTEM INSTALLATION AT INDONESIAN ISLAMIC UNIVERSITY OF YOGYAKARTA - Ismail Ismail; Fatonah Fatonah; Muhamad Yusuf; Maisah Maisah; Fadlilah Fadlilah (Dinasti International Journal of Education Management And Social Science, 2022)
Building strategic feasibility towards improving the quality of higher education institutions is a must for every higher education institution so that they are able to compete and adapt to various dynamics of contestation, technological change, as well as socio-economic and cultural changes. This study uses a qualitative method with a case study design at UII Yogyakarta, as one of the oldest private universities in Indonesia. Data were collected through interviews, documentation and direct observation. The findings show that the implementation of the internal quality assurance system in UII Yogyakarta is carried out through an ongoing process phase that improves the quality of the education process through decision making, implementation, evaluation, management and improvement. The quality assurance cycle is a process that helps ensure that the quality of a product or service is high. The SPMI Study Program at UII Yogyakarta is carried out by the Quality Assurance Cluster System organization (SGPM) in coordination with the Quality Assurance Agency of the Islamic University of Indonesia (BPM-UII) in which the quality assurance (QA) specialist is responsible for planning and implementing a quality assurance system that is comprehensive and complete.. The SPMI cycle consists of nine steps or stages, namely: standard setting process, implementation, and monitoring of a project which are essential to ensuring quality, self-evaluation and internal quality audit which are also important ways to ensure that the project remains on track., formulation of corrections, and in order to improve the quality of service delivered to stakeholders, it is important to ensure that everyone is satisfied with the results.. Utilization of the results of the implementation of SPMI at UII Yogyakarta is carried out internally to improve the performance of study programs.